1999
DOI: 10.1007/s002489900158
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Interactions in Early Life Stages of Marine Cold Water Fish

Abstract: > Abstract The intensive rearing of various fish species in aquaculture has revealed intimate relationships between fish and bacteria that eventually may affect establishment of a "normal" mucosal microflora or result in disease epizootics. Interactions between bacteria and mucosal surfaces play important roles both at the egg and larval stages of marine fish. Bacterial adhesion and colonization of the egg surface occur within hours after fertilization. The diverse flora which eventually develops on the egg ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
338
2
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(362 citation statements)
references
References 222 publications
7
338
2
5
Order By: Relevance
“…Here, we showed a significant correlation between the incidence of Saprolegniosis and the richness and evenness of specific bacterial genera associated with salmon eggs. These results indicate that along with established factors influencing disease susceptibility, such as genetic inheritance (broodstock effect), developmental stage of the salmon eggs, environmental and other stress conditions (Hansen and Olafsen, 1999), the microbiota are also a determining factor in health and disease of fish eggs that have an immature adaptive immune system and depend on other defences for protection. In terms of genetic inheritance, components of the complement immune system were shown to be maternally transferred to the eggs for rainbow trout, zebrafish and amphibian eggs (Lovoll et al, 2006;Poorten and Kuhn, 2009;Wang et al, 2009;Walke et al, 2011), and a paternal genetic component contributed to resistance against Saprolegnia in frog eggs (Sagvik et al, 2008).…”
Section: Microbial Landscapes Of Fish Eggs Y Liu Et Almentioning
confidence: 93%
See 1 more Smart Citation
“…Here, we showed a significant correlation between the incidence of Saprolegniosis and the richness and evenness of specific bacterial genera associated with salmon eggs. These results indicate that along with established factors influencing disease susceptibility, such as genetic inheritance (broodstock effect), developmental stage of the salmon eggs, environmental and other stress conditions (Hansen and Olafsen, 1999), the microbiota are also a determining factor in health and disease of fish eggs that have an immature adaptive immune system and depend on other defences for protection. In terms of genetic inheritance, components of the complement immune system were shown to be maternally transferred to the eggs for rainbow trout, zebrafish and amphibian eggs (Lovoll et al, 2006;Poorten and Kuhn, 2009;Wang et al, 2009;Walke et al, 2011), and a paternal genetic component contributed to resistance against Saprolegnia in frog eggs (Sagvik et al, 2008).…”
Section: Microbial Landscapes Of Fish Eggs Y Liu Et Almentioning
confidence: 93%
“…Over the past years, several studies have unequivocally shown that microbes play a pivotal role in the protection of eukaryotes (humans, plants and insects) against pathogens (Round et al, 2010;Mendes et al, 2011;Weiss and Aksoy, 2011;Everard et al, 2013;Stecher et al, 2013;Turner et al, 2013). For fish and amphibians, microbiome studies have only been initiated recently (Cahill, 1990;Hansen and Olafsen, 1999;Schulze et al, 2006;McKenzie et al, 2012). Several studies have indicated that specific bacteria can contribute to the protection of fish and amphibians against fungal and oomycete pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial colonization of the vertebrate gut begins at birth through contact with parents and the external environment (Bergh, 1995;Hansen and Olafsen, 1999;Dominguez-Bello et al, 2010;Pantoja-Feliciano et al, 2013). Colonization continues throughout life by microbes from ingested materials, such as food and liquid, or via contact with microbes on other organisms or abiotic surfaces (Liston, 1956;Campbell and Buswell, 1983;Meadow et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been several reports showing that the intestinal microflora of sea-water fish is dominated by members of the family Vibrionaceae and that the gut microflora plays an important role in the health of early life stages of fish (Hansen & Olafsen, 1999 ;Ring & Birkbeck, The EMBL accession numbers for the 16S rDNA sequences of strains LMG 19839 T , LMG 19840 and LMG 19842 are respectively AJ316208, AJ316207 and AJ437193.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that phenotype-based fingerprinting techniques applied in many previous studies have hampered the correct taxonomic identification of several taxa (Cerda ' -Cue! llar et al Hansen & Olafsen, 1999 ;Onarheim et al, 1994 ;Ring & Birkbeck, 1999). The usefulness of genomic fingerprinting techniques such as amplified fragment length polymorphism (AFLP), pulsed-field gel electro-F. L. Thompson and others phoresis and repetitive elements palindrome PCR for studies on bacterial evolution, phylogeny and taxonomy have recently been recognized (Rademaker et al, 2000 ;Van Belkum et al, 2001).…”
Section: Introductionmentioning
confidence: 99%